The Politics of Preaching: A New Zealand Megachurch and the Place of Current Affairs in Religious Communication - Tolmie, Duncan (Auckland University of Technology, 2023)
This research detangles the place of current affairs within religious communication. Focusing on sermons, a phenomenon with limited research in a New Zealand context, it explores the role of preaching in defining social issues, locating sources of truth, and creating and reinforcing barriers to belonging. Using a case study of City Impact Church, a New Zealand-based megachurch, this research employs a mixed method approach. Quantitative content analysis and thematic analysis are applied to probe the sermons of a senior pastor over a two-and-a-half-year period, from January 2020 to July 2022. This era included a general election and was riddled with contention for those who opposed the New Zealand Government’s response to the Covid-19 pandemic. Three important findings are discovered. Firstly, spikes in discourse regarding current affairs are linked to times when debate was rife in the public arena. The frequency and intensity of engagement between these issues suggest the pastor’s desire to impose his worldview onto the congregation. When such topics are engaged in a manner that is persistent and dogmatic, it indicates that pastors are cultivating uniformity to create unity. Secondly, the pastor positioned himself as the sole source of truth. Sermons were used to erode faith in trusted pillars of society, specifically, the mainstream media, government, and education. The pastor became a self-appointed journalist, evaluating fact from fiction on behalf of congregants. His opinions were styled as biblical truths by postulating himself as God’s mouthpiece, positioning himself as a shepherd, and assuring people of his credibility, among other tactics. Finally, the study explores barriers to belonging, which are unspoken beliefs and behaviours people must embrace to feel a sense of belonging in a group. City Impact Church’s pastor used sermons to extend barriers to belonging to include one’s opinions regarding current affairs, namely sharing views on Covid-19 vaccines, politics, and belief in the world's imminent end. Ultimately, this study calls for pastoral reflection, critical evaluation of sermon content related to current affairs, and the analytical assessment of barriers to belonging within churches, to ensure healthy faith environments are fostered.